Compliance on the Use of Different Types of Face Mask by Healthcare Workers and General Public in Tertiary Care Hospital of RMU during COVID-19 Pandemic - Saba Sarfraz ,Muhammad Raheel Raza ,Khizar Aziz ,Muhammad Umar ,Khola Noreen ,Malik Shehryar (Journal of Rawalpindi Medical College, 2020)
Objective: To determine the compliance on the use of different types of facemask among HCWs, patients and the general public in different hospital settings of tertiary care hospital of RMU during COVID-19 pandemic Material and Methods: Cross-sectional descriptive study was done among 397 study subjects of either gender consisting of HCWs, patients, and the general public visiting the tertiary care hospital from 6th April-6th June 2020. Subjects were enrolled through convenience non-probability sampling. Data was gathered by a self-structured proforma. The study consisted of questioning the frequency of washing hands, using hand sanitizers, practicing physical distancing, using eye protection goggles or face shields, the practice of sterilizing or changing of shoes and clothes after coming back to home, frequent use of disposable gloves, use of caps or head covers and water-repellant aprons and gowns. Data were analyzed by SPSS version 25.0. Results: A total of 397 study subjects including 206 (52%) males and 190 (48%) females were enrolled in the study. 118 (29.7%) had an underlying disease, 93 (78.8%) of them showed regular use of masks. The mean age of participants was 34.7 ± 12.2 years. 90.4% of study subjects had good compliance with using face masks in hospital settings, 25.9% study subjects used respirator type of masks while the use of homemade cloth was 4.8%. A total of 57.8% of study subjects had use of single masks, 22.5% used double masks, and 10.4% people used triple masks remaining 9.3% uses no masks at all. Among 189 HCWs 54% were using respirator type of masks and 46% were using surgical masks. The general public preferred to use locally made surgical masks or homemade cloth because they are cheap and easily available. Conclusion: The selection and use of PPE especially facemasks vary among HCWs and non HCWs. Even among HCWs usage varies according to the type of healthcare workers and the working environment. Overall compliance with the use of face masks and other PPE was considerably low among non HCWs. Our study has provided preliminary data about the usage of masks among HCWs and non HCWs. Longitudinal studies must be conducted to collect better evidence about the use of the face mask as PPE and its associated factors.